No need of glucocorticoid dose adjustment in patients with adrenal insufficiency before COVID-19 vaccine. Issue 1 (1st June 2022) - Pilli, Tania; Dalmiglio, Cristina; Dalmazio, Gilda; Sagnella, Alfonso; Forleo, Raffaella; Brilli, Lucia; Maino, Fabio; Ciuoli, Cristina; Castagna, Maria Grazia
Abstract: Objective: Coronavirus disease-2019 (COVID-19) causes acute respiratory distress syndrome. Patients with adrenal insufficiency (AI) may develop severe complications due to this infection and should undergo COVID-19 vaccination; however, there is no consensus about the management of their replacement therapy. The aim of our study was to evaluate the tolerability and need for glucocorticoid dose adjustment related to COVID-19 mRNA vaccines in a cohort of patients with AI. Design and methods: We prospectively administered to 88 patients (51 M/37 F; mean age: 62.3 ± 16 years), with AI (28 primary and 60 secondary AI), a questionnaire about the occurrence, severity and duration of the side effects and the need for glucocorticoid dose adjustment within 1 week after the first and the second dose of COVID-19 mRNA vaccines (Pfizer–BioNTech and Moderna). Results: Side effects of mild to moderate severity occurred in about 70% of patients after both vaccine doses. The most common adverse events were pain at the injection site, fatigue, fever and flu-like symptoms. The occurrence and severity of the side effects were not correlated to gender, type of AI and mRNA vaccine, but their total number was higher after the second vaccine dose. Doubling the oral glucocorticoid dose was needed in up to 8% of patients, especially after the second vaccine dose, but no parenteral administration was required. Conclusions: COVID-19 mRNA vaccines were well tolerated in patients with AI. Side effects were similar to those observed in the general population, and increasing glucocorticoid replacement therapy before vaccine administration was not needed.